Comicmart: Digital Comic Aggregator Platform With Monetization Schemes For Local Artists - Ng, Zhen Hao; Raja Ikram, Raja Rina; Md. Bohari, Nor Mas Aina; Ngo, Hea Choon; Salahuddin, Lizawati; Hassan, Nor Hafeizah (World Academy of Research in Science and Engineering, 2020)
This paper proposes ComicMart, a system that provides digital alternative to comic publisher who usually sells their work in physical form. Methodology used in the study was survey through convenience sampling. Requirements elicitation was conducted using surveys. Questionnaires were distributed to comic hobbyists and enthusiasts to collect feedback and opinion on the current implementation and proposed design. The study done shows that out of 53 respondents, the perceived rate of users who thought that printed comic books are getting expensive was 77.3%. A design of ComicMart was then proposed from the respondents’ feedback. Finally, an implementation prototype was developed. Most of the comic enthusiasts believed that comic books in the form of print media is getting too costly and not affordable. However, by selling the digital version of the comics, the price can be reduced, and people could afford them to buy them. The proposed project is supposed to replace physical comic bookstores with digital distribution medium. Freelancer artists who wish to promote themselves also can upload their works to the website and make it free-to-read for everyone.